A screening method for the detection of Brucella antibodies in human serum. - Hinchliffe, P M (1975)
The antiglobulin consumption test of Steffen (1954) has been adapted for the detection of Brucella antibodies in human serum. This screening method takes approximately two hours to complete and sera which give a negative result need no further investigations, whilst positive sera should be fully tested by the conventional Brucella serology technique.